Procesos biotecnológicos In Vitro para la formación de callos a partir de tejidos foliares de cafeto (Coffea arabica L.) - Diaz Sigcho, Tania del Pilar (2019)
This research study included both field and laboratory work during the period between May 2015 and January 2016. The field work entailed the gathering of vegetal material from a coffee sector of the Nambacola parish, which is part of the canton of Gonzanamá in the province of Loja. In a Plant Micropropagation Laboratory, two study phases were carried out, which included the disinfection of the plant material brought from the field as well as the application of auxins and cytokinins for the formation of calluses. In the first lab phase of disinfection, three concentrations of calcium hypochlorite were applied (15, 20 and 25%) in two immersion times (10 and 20 min), which produced a completely random design with a factorial arrangement of 3x2, six treatments, and three repetitions that evaluated the contamination of the explants. The analysis displayed an interaction between calcium hypochlorite and the immersion time, this determined that the treatment with the lowest percentage of contamination was T5 (25% Ca (ClO) 2 + 10 min) with a value of 37.62% with significant differences compared to T2 (15% Ca (ClO) 2 + 20 min) and T4 (20% Ca (ClO) 2 + 20 min), which showed a contamination of 86.19% and 74.76% respectively. T1, T3, and T6 treatments did not show significant differences in percentage of contamination. In the second lab phase, which was about in vitro callus formation of explants, a mixture of two growth hormones was used, namely, auxin: 2,4-dichlorophenoxyacetic acid (2,4-D) in concentrations of 1.0; 3.0; 3.0 and 6.0 ppm and a cytokinin: benziladenine (BAP) in three concentrations of 3.0; 10.0; 0.0 and 0.0 ppm ppm respectively. Also, a completely randomized design was established, where callus formation was evaluated in explants of Coffea arabica L. The treatment with the highest percentage of callus was T1 (1.0 ppm 2,4-D +3.0 ppm BAP), which was obtained through the analysis of variance (ANOVA) that determined that the treatments they presented high variability among them. In the same way the Tukey test showed significant differences between treatments with a p = <0.05. It should be noted that treatments without cytokinins (BAP) did not present callus formation. According to the days evaluated, the appearance of stranding was evident on the twentieth day of evaluation for treatments T1 and T2 with percentages of 60 and 20% respectively, while T3 and T4 did not present any value for this indicator. Stranding was stabilized at 30 days of evaluation in T1 and T2 reaching values of 73.33 and 26.67% respectively, on the other hand treatments T3 and T4 did not present callus formation. The calluses obtained showed homogenous as well as an inhomogeneous formation. For instance, the explants that formed calluses in T1 (1.0 ppm 2,4-D +3.0 ppm BAP) presented percentage values of 66.7 and 33.33 of homogenous and inhomogeneous callus respectively when comparing to T2 (3.0 ppm 2,4-D +10.0 ppm BAP) which presented a 100% non-homogeneous callus. In the present research work, disinfection and in vitro propagation protocols were generated in the Coffea arabica L. species, to contribute toward future in vitro studies for the of coffee trees. Keywords: Coffea arabica L., in vitro, spread.